Immediate versus delayed single blastocyst transfer following the first stimulated IVF cycle in the freeze-all strategy: a study protocol for a randomised controlled trial - He Li; Lu Li; Xiaoxi Sun; Xiang Lu; Wenbi Zhang; Junling Chen; Ernest HY Ng (BMJ Open)
Introduction In recent years, the use of frozen embryo transfers (FET) has rapidly increased following the freeze-all strategy due to the advantages of increased maternal safety, improved pregnancy rates, lower ectopic pregnancy rates and better obstetric and neonatal outcomes. Currently, there is still no good scientific evidence to support when to perform FET following a stimulated in vitro fertilisation (IVF) cycle in the freeze-all strategy.Methods/analysis This will be a randomised controlled trial. A total of 828 women undergoing their first FET following their first stimulated IVF cycle in the freeze-all strategy will be enrolled and randomised into one of the following groups according to a computer-generated randomisation list: (1) the immediate group, in which FET will be performed in the first menstrual cycle following the stimulated IVF cycle; or (2) the delayed group, in which FET will be performed at least in the second menstrual cycle following the stimulated IVF cycle. The primary outcome will be live birth, which is defined as the delivery of any infants at ≥22 gestational weeks with heartbeat and breath.Ethics/dissemination Ethical approval was granted by the Ethics Committee of Assisted Reproductive Medicine at the Shanghai JiAi Genetics & IVF Institute (JIAI E2019-15). Written informed consent will be obtained from each woman before any study procedure is performed, according to good clinical practice. The results of this trial will be disseminated in a peer-reviewed journal.Trial registration number NCT04371783